Press Freedom and National Security: The Place of Human Rights in Nigeria’s Cybercrime Laws - Antai, Godswill Owoche; Obisesan, Olawunmi Opeyemi; Umo, Maria Edet; Ismaila, Hassan; Okpong, Dennis Edet (NIU Journal of Social Sciences, 2025)
The study addresses the nexus of press, national security and human rights as found in Cybercrime (Mediation, Prevention, etc.) Law 2015, Nigeria. It delves into the experiences of Nigerian law against cybercrimes like cyberstalking, identity theft and online terrorism on freedom of expression and work of journalists. Even though the government justified the Act as a vital way to fight cyber terrorism and protect national security, critics have suggested its broad and vague provisions have been weaponized as one mechanism for the press freedoms and democracy rights. The research avertedly points out some provisions of the law, foremost among which one is section 24 of the Cybercrime (Mediation, Prevention, etc.) Law 2015, which talks about cyberstalking which can be used most by journalists/bloggers/activists who dare criticize government policy or expose corruption. It further examines the duty of courts, activists and international human rights norms in securing press freedom as well a reasonable response to genuine security concerns. Through a comparative study of Nigerian practices with other countries on the continent, including South Africa and Kenya, the research finds best practice in reconciling national security with press freedom. The study concludes by suggesting legislative reforms; judicial review of the discretion of police officers and an active civil society to ensure that cybercrime laws of Nigeria heed international human rights obligations whilst balancing press freedom in the digital age. Keywords: Cybercrime, cyberstalking, online terrorism, press fredom